Container Dan Pembungkusan Hasil-Hasil Industri Ringan Dan Kerajinan Rakyat - Toebin Toebin (Jurnal Kimia dan Kemasan, 1978)
The packaging's function are: to protect mechanical force, to protect contamination , sales promotion , and as a unit of measurement. The types of packaging materials are : papers, plastics, plastic bags textile bags, cartons (plain and corrugated), wood boxes, etc. Whereas the types of container are glass container , plastic containers, and metal containers. the principles of packaging procecses are manually or mechanically.